Revision of total hip arthroplasty using dual mobility acetabular cup as treatment of recurrent hip dislocation following total hip arthroplasty: a case report - Daniati, Sonia; Dusak, I. Wayan Suryanto (International Journal of Research in Medical Sciences, 2024)
One of the most common causes of revision surgery after total hip arthroplasty (THA) is dislocation. We present a recurrent case of hip dislocation following THA treated with dual mobility cup. Treated with total hip arthroplasty in another hospital in January 2024. Following the first surgery he suffered from a first event of hip dislocation in February 2024, managed with open reduction. One week following the open reduction, the hip became dislocated again and was treated with closed reduction. Two months later he was referred to our center with recurrent posterior right hip dislocation. Revision surgery was performed, using dual mobility acetabular cup. Intraoperative evaluation showed adequate stability and limb length was acceptable. Partial weight-bearing and active range of motion exercise was initiated following the surgery. Dual mobility acetabular cup reduces rate of dislocation and has satisfactory mid-term outcome.